Consumer Protection From Default Of Sharia Housing Developer Agreement - Sekar Anindita Candra Utami (Green Publisher Indonesia, 2024)
Consumers frequently face issues with defaults on housing agreements, often driven by attractive low prices and developers leveraging sharia concepts. PT Fimadani Graha Mandiri (FGM), based in Bekasi, exemplifies this trend, utilizing Binding Sale and Purchase Agreements (Akad Istishna) and Sale and Purchase Agreements on Credit and Installments (Al-Bay' Bi Ad-Dayn Wa Bi At-Taqsith). These agreements delineate the rights and obligations of both developers and consumers. This study aims to analyze consumer protection within these agreements, focusing on safeguarding consumers against developer defaults and examining legal protections in consumer default lawsuits. Employing a doctrinal law method, the research synthesizes relevant rules, principles, and norms. Findings indicate that consumer protection mechanisms in these agreements include the right to accurate information, the ability to select products according to personal preferences, compensation for discrepancies in specifications, and timely delivery of housing. However, the effectiveness of consumer protection in judicial outcomes remains suboptimal. In several cases, PT FGM has denied compensation and refunds, citing a lack of funds and assets. Consequently, consumers face challenges in executing legal claims due to the inability to ascertain the company's assets. This analysis underscores the need for enhanced consumer protections and more effective judicial remedies to address defaults in housing agreements.